Secularism and Islam in Bangladesh: 50 years after independence - Abdul Wohab (Routledge South Asian religion series, 2023)
1. Secularism and Islam in Bangladesh -- 2. Revisiting Worldviews on Secularism and Religiosity: West and Beyond -- 3. Secularism in a Historical Form: Syncretistic Islam in Medieval to the 19th century Bengal -- 4. Transformation of Secularism: 20th and 21st century Bangladesh -- 5. Islam and Secularism? The Role of State, Religion and Political Parties in Bangladesh -- 6. Future of Secularism: Bangladesh and Beyond -- 7. Conclusion -- Appendix -- Index -- References.